Real-world Outcomes of Multiple Myeloma: Retrospective Analysis of the Czech Registry of Monoclonal Gammopathies - Hájek, Roman; Jarkovsky, Jiri; Maisnar, Vladimír; Pour, Ludek; Špička, Ivan; Minařík, Jiri; Gregora, Evžen; Kessler, Petr; Sýkora, Michal; Fraňková, Hana; Campioni, Marco; DeCosta, Lucy; et al. (Clinical lymphoma, myeloma & leukemia, 2018)
INTRODUCTION: Real-world data on patient outcomes and treatment patterns in multiple myeloma (MM) are limited. MATERIALS AND METHODS: The present noninterventional, observational, retrospective analysis of prospectively collected Czech patient medical record data from the Registry of Monoclonal Gammopathies estimated real-world outcomes in adults with a diagnosis of symptomatic MM made between May 2007 and June 2014. RESULTS: In total, 2446 patients had initiated first-line treatment. The median overall survival since the diagnosis (primary endpoint) was 50.3 months (95% confidence interval, 46.1-54.5 months) and decreased with each successive treatment line. A similar trend was observed for progression-free survival and the depth of response. In line with European guidelines and clinical practice, bortezomib-, thalidomide-, and lenalidomide-based regimens were most commonly used across all treatment lines (42.3%, 28.9%, and 18.4%, respectively). In the first line, bortezomib and thalidomide were used most often, with lenalidomide the most commonly used agent in the relapse setting (second to fourth lines). Exploratory analyses revealed that younger age (≤ 65 years), lower international staging system stage, and previous stem cell transplantation were associated with significant improvements in overall and progression-free survival, especially in the early treatment lines. CONCLUSION: The present study is the first analysis of Czech data from the Registry of Monoclonal Gammopathies, and it provides important insights into the real-world management of MM for physicians and healthcare providers.
Keywords: senioři; analýza přežití; Thalidomide; Survival; MM; transplantace kmenových buněk; senioři nad 80 let; Multiple Myeloma; thalidomid; Retrospective Studies; Survival Analysis; doba přežití bez progrese choroby; Česká republika; Bortezomib; Middle Aged; registrace; mužské pohlaví; RMG; Prospective Studies; Czech Republic; Treatment patterns; Registries; Follow-Up Studies; věkové faktory; následné studie; Lenalidomide; Aged, 80 and over; Neoplasm Staging; mnohočetný myelom; ženské pohlaví; bortezomib; retrospektivní studie; prospektivní studie; Humans; Stem Cell Transplantation; Progression-Free Survival; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; Age Factors; staging nádorů; protokoly protinádorové kombinované chemoterapie; Female; Aged; lenalidomid; lidé; Male